ISA AL-MASIH DALAM TINJAUAN ISLAM DAN KRISTEN - Indra Harahap; Abu Sahrin; Hapni Sartika Siregar (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2022)
The main problem in this research, discusses "Isa Al-Masih in Review of Islam and Christianity", while the main problems of the research are divided into two sub-problems, namely: 1) What are the views of Islamic and Christian religious figures about the history of Jesus Christ. 2) What is the position of Jesus Christ in Islam and Christianity. The approach used in this research is a comparative approach. as for the source of research data is the primary data obtained in this study is the Qur'an and the Bible (New Testament). and secondary data, namely the sources obtained from books, journals, articles, and other information related to the position of Jesus Christ in the Qur'an and the New Testament. The results of this study are the position of Isa Al-Masih in the Qur'an is Jesus as the messenger of Allah. Islam believes that Jesus is the Prophet and Messenger of Allah and the last among the Children of Israel. title as Ulul Azmi a special title for the apostle class who has extraordinary fortitude. have miracles of proof of the truth of the Prophets, extraordinary things seem to happen and what the Prophet said is true, he is my messenger and the proof is that miracle. Meanwhile, the position of Jesus in the New Testament as the god of Christians admits that they believe in Isa is contained in a teaching built by Paul. and the name Isa is not in the book because it was replaced with the name Jesus. as the Savior of mankind has sinned Jesus Christ came to the world and his death as payment or atonement for the sins of his people. Jesus' resurrection from the dead proved that his death was sufficient to pay the debt of sin or penance.